2020
DOI: 10.1016/j.xcrp.2020.100257
|View full text |Cite
|
Sign up to set email alerts
|

Light-Emitting Probes for Labeling Peptides

Abstract: SUMMARY Peptides are versatile biopolymers composed of 2–100 amino acid residues that present a wide range of biological functions and constitute potential therapies for numerous diseases, partly due to their ability to penetrate cell membranes. However, their mechanisms of action have not been fully elucidated due to the lack of appropriate tools. Existing light-emitting probes are limited by their cytotoxicity and large size, which can alter peptide structure and function. Here, we describe the av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 95 publications
(150 reference statements)
1
13
0
Order By: Relevance
“…The peptide antibiotic polymyxin B was used as a positive control in our studies 21 . In summary, SEPs did not permeabilize the outer membrane of bacteria to the level previously reported for AMPs 7,32 or EPs 21 , indicating that the mechanism of action of SEPs might be independent of outer membrane permeabilization.…”
Section: Mechanism Of Action Of Sepssupporting
confidence: 45%
See 1 more Smart Citation
“…The peptide antibiotic polymyxin B was used as a positive control in our studies 21 . In summary, SEPs did not permeabilize the outer membrane of bacteria to the level previously reported for AMPs 7,32 or EPs 21 , indicating that the mechanism of action of SEPs might be independent of outer membrane permeabilization.…”
Section: Mechanism Of Action Of Sepssupporting
confidence: 45%
“…Current methods used to discover new molecules rely primarily on prospection of naturally occurring organisms, which is slow and upredictable as it relies on trial-and-error experimentation. Additional engineering of AMPs has leveraged heuristics whereby amino acid residues substitutions are introduced [7][8][9][10][11] , guided by alterations in physicochemical feature determinants known to contribute to membrane targeting and, ultimately, antimicrobial activity 4 . Recently, advances in machine learning 12,13 and methods 14 such as generic algorithms 15 and pattern recognition algorithms 16,17 have yielded improved peptides.…”
Section: Introductionmentioning
confidence: 99%
“…47 19 F NMR showed that such linkers possess significant rigidity and lipophilicity. 48 By using fluorescent reporters, 49,50 we further assessed their modes of action involving outer and inner membrane permeability and change in membrane potential. The HIM imaging analysis further identified the bacterial morphological changes caused by PrAMPs 6 and 7 .…”
Section: Discussionmentioning
confidence: 99%
“…If the role of triplet states is confirmed, this should be considered in the future use of lophine silylperoxides as sensors for biological systems . The conjugation of a lophine silylperoxide to a peptide or protein would allow the use of this class of peroxides as CL probes for labeling biomolecules . While singlet excited states are important for analytical and labeling purposes, , triplet states generated in situ could be used for assessing biological oxidation through chemiexcitation instead of light absorption, also known as “dark” photochemistry.…”
Section: Resultsmentioning
confidence: 99%